Acteoside relieves mesangial cell injury by regulating Th22 cell chemotaxis and proliferation in IgA nephropathy. (15th October 2018) - Gan, Lu; Li, Xiaozhao; Zhu, Mengyuan; Chen, Chen; Luo, Huimin; Zhou, Qiaoling
Abstract: The existing therapies of IgA nephropathy are unsatisfying. Acteoside, the main component of Rehmannia glutinosa with anti-inflammatory and anti-immune effects, can improve urinary protein excretion and immune disorder. Th22 cell is involved in IgA nephropathy progression. This study was determined to explore the effect of acteoside on mesangial injury underlying Th22 cell disorder in IgA nephropathy. Serum Th22 cells and urine total protein of patients with IgA nephropathy were measured before and after six months treatment of Rehmannia glutinosa acteoside or valsartan. Chemotactic assay and co-culture assay were performed to investigate the effect of acteoside on Th22 cell chemotaxis and differentiation. The expression of CCL20, CCL22 and CCL27 were analyzed. To explore the effect of acteoside on mesangial cell injury induced by inflammation, IL-1, IL-6, TNF-α and TGF-β1 were tested. Results showed that the proteinuria and Th22 lymphocytosis of patients with IgA nephropathy significantly improved after combination treatment of Rehmannia glutinosa acteoside and valsartan, compared with valsartan monotherapy. In vitro study further demonstrated that acteoside inhibit Th22 cell chemotaxis by suppressing the production of Th22 cell attractive chemokines, i.e., CCL20, CCL22 and CCL27. In addition, acteoside inhibited the Th22 cell proliferation. Co-culture assay proved that acteoside could relieve the overexpression of pro-inflammatory cytokines, and prevent the synthesis of TGF-β1. TGF-β1 level in mesangial cells was positively correlated with the Th22 cell. This research demonstrated that acteoside can alleviate mesangial cell inflammatory injury by modulating Th22 lymphocytes chemotaxis and proliferation.